A bibliometric analysis of studies on environmental enrichment spanning 1967–2024: patterns and trends over the years - Singhal, Gaurav; Baune, Bernhard T. (Frontiers in Behavioral Neuroscience, 2024)
Environmental Enrichment (EE) has received considerable attention for its potential to enhance cognitive and neurobiological outcomes in animal models. This bibliometric analysis offers a comprehensive evaluation of the EE research spanning from 1967 to 2024, utilizing data extracted from Scopus and analyzed through R and VOSviewer. The volume of publications, citation patterns, and collaborations were systematically reviewed, highlighting important contributions and emerging trends within the field of animal research. Core concepts of EE research are mapped, revealing key themes such as neuroplasticity, cognitive function, and behavioral outcomes. A significant increase in EE research is demonstrated, particularly after the year 2000, reflecting growing scientific and public interest in EE paradigms. This analysis provides insights into the global contributions and collaborative networks that have shaped EE studies over time. The role of EE in advancing the understanding of neurobiological, neurodevelopmental, and neurodegenerative processes is underscored. Influential contributors, leading countries, and high-impact journals in the field of EE are identified, offering a valuable resource for researchers seeking to understand or extend the current knowledge base. The strategic selection of keywords and rigorous data curation methods ensure that the findings accurately reflect the most impactful aspects of EE research in animals. This study serves as an essential reference for future explorations and applications of EE across disciplines. By providing a clear and structured overview of the field, this paper aims to serve as a foundation for ongoing and future research initiatives, encouraging more robust investigations and applications of EE to enhance cognitive and neurological health globally.